Recession, local employment trends and change in self-reported health of individuals: A longitudinal study in England and Wales during the 'great recession'. (September 2019) - Curtis, Sarah; Norman, Paul; Cookson, Richard; Cherrie, Mark; Pearce, Jamie
Highlights: Study of England and Wales. Trajectory modelling of local area employment trends in the great recession 2007–2011. Multivariable regression modelling of change in individual self-reported illness 2001–2011. Various other individual and local area risk factors are controlled for in models. Local employment trends predict 'new' cases of long term illness.